Answer:
[tex]x\cdot (y\cdot 3)=(x\cdot y)\cdot 3[/tex] Associative Property of Multiplication
[tex](x+y)+3=3+(x+y)[/tex] Commutative Property of Addition
[tex](x+y)+3=x+(y+3)[/tex] Associative Property of Addition
[tex]x\cdot (y\cdot 3)=x\cdot (3\cdot y)[/tex] Commutative Property of Multiplication
Step-by-step explanation:
Associative Property of Addition: [tex](a+b)+c=a+(b+c)[/tex]
Associative Property of Multiplication: [tex](a\cdot b)\cdot c=a\cdot (b\cdot c)[/tex]
Commutative Property of Addition: [tex]a+b=b+a[/tex]
Commutative Property of Multiplication: [tex]a\cdot b=b\cdot a[/tex]
Then
Expression Property
[tex]x\cdot (y\cdot 3)=(x\cdot y)\cdot 3[/tex] Associative Property of Multiplication
[tex](x+y)+3=3+(x+y)[/tex] Commutative Property of Addition
[tex](x+y)+3=x+(y+3)[/tex] Associative Property of Addition
[tex]x\cdot (y\cdot 3)=x\cdot (3\cdot y)[/tex] Commutative Property of Multiplication